A comparative study between fat myringoplasty and temporalis fascia tympanoplasty in moderate to large central perforation of pars tensa of tympanic membrane - Ambani, Kirti P.; Gangwani, Rachana W.; M., Bhavya B.; Vakharia, Sanket D.; Katarkar, Ashish U. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: To compare the efficacy between fat graft (FG) and temporalis fascia (TF) graft in tympanic membrane perforations larger than 4mm size or involvement of >25% of tympanic membrane. Methods: This prospective study was carried out during December 2015 to January 2016, for a period of 13months at our Otolaryngology Department. All study patients, who fit into inclusion and exclusion criteria, were divided into two groups according to the type of graft material taken. In group- 1temporalis fascia (TF) graft was taken while in group- 2 fat graft (FG) was taken. An evaluation of hearing was done with full Audiometric and Eustaschian tube function testing. All laboratory preoperative testing was done. Postoperative follow up was done at 2nd, 3rd and 5th month’s period and sos, graft status and hearing evaluation with PTA for all four frequencies 500, 1000, 2000 and 4000 Hz with air conduction and bone conduction thresholds were recorded and compared with preoperative PTA records in both groups. Results: In TF group total 24 (80%) patients had graft uptake, 4 (13.3%) patients had residual perforation and 2 (6.6%) patients had graft failure due to postoperative infection. In FG group total 16 (53.3%) patients had graft uptake, 6 (20%) patients had graft medialised and necrosed, 6 (20%) patients had residual perforation and 2 (6.6%) patient had graft rejection due to postoperative infection. Graft uptake rate in group 1 was 80% while in group 2 was 53.3%. Mean preoperative ABG in TF group was 25±17 dB and mean postoperative ABG was 10±02 dB, in fat graft technique mean preoperative ABG was 25±13 dB and mean postoperative ABG was 16±15 dB. Fat graft technique is simple, quick and minimally invasive. It doesn’t require middle ear manipulation. Conclusions: There is no ideal material for tympanic membrane repair but for moderate to large perforation temporalis fascia graft is better than fat graft in terms of healing and hearing outcomes but considering morbidity fat gives less morbidity.